Protocol‐Driven Best Practices and Cardiogenic Shock Survival in Asian Patients - Calvin Leung; Yan Hang Fong; Michael Chi Shing Chiang; Ivan Man Ho Wong; Cheuk Bong Ho; Yin Kei Yeung; Chung Yin Leung; Pok Him Lee; Tai Chung So; Yuet Wong Cheng; Shing Fung Chui; Alan Ka Chun Chan; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Cardiogenic shock carries high mortality. This study investigated the relationship between protocol‐advocated best practices and outcomes. Methods Patients with cardiogenic shock supported by Impella CP in an Asian tertiary cardiac center were evaluated for 30‐day post percutaneous ventricular assist device (PVAD) survival after adopting a standardized protocol emphasizing early mechanical circulatory support (shock‐to‐PVAD time ≤180 minutes), pulmonary artery catheterization for invasive hemodynamics, and safe vascular access. Results Of 109 consecutive patients (mean age 58.5±11.2, 80.7% male, 67% acute myocardial infarction, 33% acute decompensated heart failure), 45 (41.3%), 33 (30.3%), and 31 (28.4%) were in SCAI Shock Stages C, D, and E, respectively. A suggestive trend of improving 30‐day survival was observed (56.8%, 63.9%, and 72.2% in successive one thirds, P1, P2, and P3 of patients), paralleling a similar trend in achievement of best practices. Patients achieving all 3 best practices significantly increased from 35.1% (P1) to 52.8% (P3) (P=0.026). Median shock‐to‐PVAD time reduced from 5 [interquartile range: 2–23] hours (P1) to 1.5 [1–5] hours (P3) (P for trend=0.014), whereas pulmonary artery catheterization utilization (80.6–86.1%) and device‐related major vascular complications (5.6–8.4%) remained relatively stable. Achieving more best practices was significantly associated with better 30‐day survival, with patients achieving all 3, 2, and ≤1 best practices had 30‐day survival rates of 75.0%, 63.6%, and 35.7%, respectively (P=0.043). In multivariate Cox regression analysis, shock‐to‐PVAD time >180 minutes remained an independent predictor of mortality (P=0.031). Conclusions Achievement of protocol‐advocated best practices, especially early shock recognition and prompt PVAD support in appropriate patients, was associated with improved outcomes with PVAD use in cardiogenic shock. Future studies are suggested to confirm the benefits of a protocolized approach and evaluate the value of individual best practices.